One piece ceramic heat exchanger for concentrating solar power electric plants. (November 2020) - Singh, Dileep; Yu, Wenhua; France, David M.; Allred, Taylor P.; Liu, I-Han; Du, Wenchao; Barua, Bipul; Messner, Mark C.
Abstract: Using additive manufacturing techniques, a ceramic heat exchanger was optimized for a concentrating solar power (CSP) electric power plant with a corrosive molten salt at atmospheric pressure as the solar field heat transfer fluid and supercritical carbon dioxide at 200 bar as the power block fluid. Temperatures ranged from 750 °C to 540 °C. The plant heat exchanger was optimized for heat transfer and stress using 1 m 3 modules arranged in parallel. Heat transfer was optimized using COMSOL Multiphysics software resulting in a unique semi-elliptical cross section for the fluid flow channels in a counter-flow configuration. Counter-flow was made possible through additive manufacturing of the fluid headers as part of each modular heat exchanger thus producing the entire module as a single piece and minimizing cost. Using reasonable parametric values, a heat exchanger module was optimized to 0.5 MW/m 3, and a section of it was manufactured including the fluid headers. Parametric studies showed the potential for a module to reach 3.5 MW/m 3 . Highlights: A counter-flow heat exchanger with semi-elliptical cross section was developed. The modular ceramic heat exchanger was optimized for heat transfer and stress. The heat exchanger is an improvement to concentrating solar power applications. The heat exchanger module has a potential power density of up to 3.5 MW/m 3 .